Partisipasi Masyarakat dalam Pelaksanaan Program Desa Berdikari di Desa Ngrapah Kecamatan Banyubiru Kabupaten Semarang Tahun Pelaksanaan 2016-2017 - Kuswantoro, Agam; Tijan, Tijan; Lestari, Puji (Unnes Political Science Journal, 2017)
A self Reliant village is a program of the Central Java Provincial Government to complete poverty. Community participation is essential to run the Desa Berdikari program. The purpose of this research is to know and describe the participation of the community in the implementation and supporting factors and inhibiting the participation of the community in the implementation of the self-reliant village program in Ngrapah village in the implementation year 2016-2017. The method used in this research is qualitative with the test of data validity using source triangulation. The results of the study that the way the community participates in a self-supporting is a program of the Central Java Provincial Government program is divided into three, namely based on the organization, based on the stages of the program, and based on the shapes. Supporting factors consist of factors wanting to build the potential of Ngrapah Village and the factors of a self self-reliant village program, supplementing income and adding activities, Family support, raising the potential and development of Ngrapah Village, Assisting group members and raising village potential and learning in groups. The inhibiting factors for Kader Desa Berdikari and the people who are members of the productive economic business group are procedural factors, and funding, while the self-reliance of the community and the general public is the attention of the village government is lacking, public awareness is lacking.